Exploring the Intersection of Narcolepsy and Attention Deficit Hyperactivity Disorder: Similarities, Differences, and Clinical Implications - Sung Hoon Yoon; Young-Chan Kim; Ho Jun Seo; Tae Won Kim; Jong-Hyun Jeong; Yoo Hyun Um; Seung Chul Hong (Sleep Medicine Research, 2024)
Narcolepsy and attention deficit hyperactivity disorder (ADHD) are distinct neurobiological conditions characterized by overlapping symptoms, including excessive daytime sleepiness and cognitive dysfunction. Despite their differences in etiology and pathophysiology, recent studies have highlighted a potential association between the two disorders, with a significant prevalence of ADHD symptoms observed in narcolepsy patients. This narrative review explores the similarities and differences between narcolepsy and ADHD, focusing on their shared symptomatology, neurobiological mechanisms, challenges in diagnosis, and treatment implications. While both disorders exhibit disruptions in dopaminergic and noradrenergic neurotransmitter systems, differential diagnosis remains challenging due to overlapping clinical presentations. Polysomnography findings, such as appearance of sleep onset rapid eye movements in narcolepsy patients, provide important distinctions that enable accurate diagnosis. Treatment strategies often involve stimulant medications for symptom management; however, nonpharmacological interventions, such as cognitive behavioral therapy, have been shown to have the potential to improve patient outcomes. Clinicians must consider the possibility of coexisting narcolepsy in ADHD patients and vice versa to ensure appropriate treatment selection and optimal patient care. Further research is needed to refine diagnostic criteria, elucidate the complex interplay between the two disorders, and develop personalized therapeutic approaches. A multidisciplinary approach involving sleep specialists, neurologists, psychiatrists, and psychologists is essential to address the diverse biopsychosocial needs of patients with concurrent narcolepsy and ADHD.